PEMBINAAN LITERASI UNTUK MENANGKAL BERITA PROVOKATIF - Riana Dwi Lestari; Reka Yudha Mahardika; Via Nugraha (Abdimas Siliwangi, 2020)
This service is motivated by the problem of the number of provocative news that is distributed and published by citizens on social media (social media). Social media users can hide their identity which allows the emergence of unlimited communication that interferes with communication. There is no distance between social status and profession in social media, even the small people can easily comment instead criticize the leader directly. That is why messages written in social media can easily be spread and spread over a wide range and in a short period of time which then becomes viral (meaning to spread quickly and broadly like a virus). The purpose of this service is to explain the profile of provocative news that spreads on social media, the profile of pages that often contain provocative news, literacy development to ward off provocative news using theories of communication science, journalism, and farming. Provocative news tends to be close to hoak news, because news that contains hate speech will display fact manipulation to justify his hatred. Especially if the discourse is considered as a journalistic product (news). Whereas a news that is recognized as a journalistic product must be neutral and comply with the Journalistic Code of Ethics. Every news has different characteristics in terms of the depth of coverage, the depth of the facts, the speed of coverage, even in terms of the difficulty of reporting and writing. This service uses a qualitative approach to the method descriptive. Researchers will record in detail everything that can be achieved through empirical. The target in this service is 50 Subang District teachers. The results of this dedication can be concluded that after attending this counseling the teachers can distinguish provocative news so that they can convey their knowledge in school, especially to students.